Increasing Mathematics Learning Outcomes Through The NHT Learning Model for Students of SD Negeri 2 Keposong - Riyanto, Sri (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The lack of students' understanding of the KPK and FPB material became the background for this research. This study aims to find out whether the application of the NHT (Numbered Head Together) learning model can improve learning outcomes for Mathematics on KPK and FPB Material in Grade IV students of SD Negeri 2 Keposong in the 2021/2022 Academic Year. The type of research used is Classroom Action Research (CAR). In this study, student learning outcomes can be increased, seen from the results of formative tests in each cycle, namely in the first cycle, 18 students or 64.29% completed with an average score of 68.75. In cycle II it increased to 25 students or 89.28% with an average value of 80.36. The final score of student learning outcomes in cycle I and cycle II proves that the use of the NHT (Numbered Head Together) learning model can improve learning outcomes.